Endoscopic Ultrasound Criteria for Arterial Invasion in Pancreatic Cancer of the Body and Tail. Issue 4 (April 2020) - Yamato, Mutsumi; Mikata, Rintaro; Yasui, Shin; Iino, Yotaro; Shingyoji, Ayako; Kusakabe, Yuko; Ohyama, Hiroshi; Sugiyama, Harutoshi; Sakai, Yuji; Tsuyuguchi, Toshio; Yoshitomi, Hideyuki; Ohtsuka, Masayuki; et al.
Abstract : Objectives: We aimed to determine the difference in endoscopic ultrasonography (EUS) images between portal vein (PV) and arterial invasion of pancreatic cancer and to develop criteria for arterial involvement. Methods: We reviewed EUS data of consecutive patients who underwent distal pancreatectomy from December 2010 to May 2017. We categorized the tumor-vessel relationship into 4 and 5 types, respectively, for the PV and arteries: ( a ) clear separation between tumor and vessel; ( b ) tumor border at vessel, echo-rich vessel wall uninterrupted; ( c ) echo-rich vessel wall interrupted; ( d ) vessel contour irregularity; and ( e ) arterial wall thickening or echogenic band surrounding the artery. We compared EUS outcomes with surgical and pathological results. Results: Overall, 56 patients underwent distal pancreatectomy, of whom 22 received en bloc celiac axis resection. The pathological invasion rates of PVs and arteries were 46.2% and 0% in (c), and 72.5% and 42.4% in (d) ( P = 0.046, P = 0.016), respectively. The overall sensitivity and specificity were 92.1% and 83.2%, respectively, for diagnosing venous invasion and 70.0% and 84.4%, respectively, for arterial invasion. Conclusions: Different EUS criteria may be necessary for diagnosing arterial and portal venous invasions. Criterion (d) might be appropriate for diagnosing arterial invasion.